Pengaruh Orientasi Kewirausahaan Terhadap Kinerja Koperasi - Yanti, Dyah Agustin Widhi (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
This study aims to prove and analyze the influence of Entrepreneurship Orientation on Cooperative Organizational Performance in the city of Surabaya. The phenomenon that is happening right now is a paradigm shift in managing, that is, from a social paradigm shifted towards a professional business paradigm. The sample used was 142 cooperatives from 219 cooperatives registered at the Surabaya City Cooperative and UMKM Office. The data collection method uses a questionnaire, where the testing of instruments uses the Validity and Reliability test. Data analysis and hypothesis testing in this study used Simple Linear Regression. The results showed that the Entrepreneurship Orientation variable with indicators: confidence in the profession, task and outcome oriented, courage to take risks, leadership, future oriented and originality in creativity and innovation and cooperative performance with indicators: financial perspective, customer perspective and perspective Internal business processes significantly influence the Cooperative Organizational Performance.